EU-US differences in the size of R&D intensive firms - Raquel Ortega-Argilés; Andries Brandsma (European Commission, Joint Research Centre (JRC), 2009)
The average firm size of the top R&D investors among US-based companies is smaller than that of the EU-based firms. Does this help to explain why the US has a greater R&D intensity, or is the higher firm size in the EU, just as its lower R&D intensity, determined by the sectors in which the top R&D investors are operating? Using data on the top-R&D investors from the 2006 EU Industrial R&D Investment Scoreboard, the size differential between R&D performers in the EU and US is more closely examined. A first observation is that, despite great differences between sectors, the overall distribution of companies' R&D investments in both economies is remarkably similar, as opposed to the distribution of the R&D/sales ratios of the same two sets of companies. The notion that size plays a role, independent of the sectoral composition of R&D, is then confirmed by regression analysis. In the US as well as in the EU, smaller sized Scoreboard companies tend to spend a larger proportion of their income from sales on R&D.
Keywords: O33; 330; Research and Development intensity; EU-US R&D gap; size of firms